Prevalence of undiagnosed hypothyroidism in patients with gall bladder stones in Belagavi - Koujalagi, Ramesh S.; Karagi, Vinod; Gogate, Abhijit S.; C., Athira (International Surgery Journal, 2021)
Background: Contribution of hypothyroidism to gallstone formation is debated over years. With this background, the study intended to analyze the prevalence of undiagnosed hypothyroidism in patients with cholelithiasis. The aim is to understand the prevalence of hypothyroidism in patients with gallstones. Methods: A prospective, hospital-based study was done on 100 patients admitted for the management of gall stone disease in Belagavi. After initial screening, a detailed history was obtained with special reference to symptomatology and the risk factors as per proforma from patients meeting selection criteria. Thyroid function test was done on all eligible patients. Patients were divided into three groups of Euthyroid, Subclinical hypothyroid and clinical hypothyroidism. Statistical analysis used. Percentage of gall stones in different age groups and gender of the study population was calculated followed by prevalence of hypothyroidism and subclinical hypothyroidism in all the patients included. Results: Among the study population, 40% were male and 60% were female. 23 of them have subclinical hypothyroidism and 6 of them were diagnosed with hypothyroidism. Majority of subclinical hypothyroid patients (39.13%) were aged 41-60 years. Hypothyroid symptoms were shown by the study population with unknown thyroid status. Conclusions: The prevalence of hypothyroidism in cholelithiasis is 29% in the study and is significant. The study demands further studies to consider hypothyroidism as a cause /risk factor for biliary calculus.